Analisis Kinerja Biaya Dan Jadwal Terpadu Dengan Konsep Earned Value Method (Studi Kasus: Proyek Pembangunan Gedung ) - Mandiyo Priyo; Khairul Fajri Indraga (Semesta Teknika, 2015)
Project control necessary to track and anticipate the possibility of bad will happen in the project and take appropriate action. In project control, there are two variables that affect the success of the project that is time and cost. Control of the project carried out properly and systematically necessary to determine the performance time and cost of the project. The purpose of this study was to determine the performance of the project in terms of time and cost of completion of the project. In addition, this study aims to estimate the time and cost of completion of projects on time and to know the index is reviewed project achievements. The data used are secondary data from contractors. These data include the Budget Plan, Budget Plan of Implementation, progress reports, and time schedule. The method used to analyze the value method result (Earned Value Method) which combine aspects of the schedule, cost and time to complete the project.The analysis was performed with the help of software Microsoft Excel 2013. The results showed that the CPI and SPI values at week 28 was negative SV value (Rp. -78,827,148.63) And SPI values is 0.99 1, which means there is a delay the schedule of implementation of the plan schedule. While the value of positive CV (Rp. 2,108,709,167.60) and the CPI amounted to 1.30 1, which means more less than final cost of the budget. The estimated cost of the project required Completion is EAC (Rp. 8,400,517,603.93) and ETC (Rp. 1,253,357,227.10). While estimates of the required project completion time is 38 weeks. Value confidence index performance (TCPI 1) or value of 1.30 means there is a decrease in performance.